Technologies of refining of aluminum alloys by gas blowing - M. A. Sadokha; A. A. Andrushevich (Литьë и металлургия)
The results of the analysis of various methods of refining aluminum alloys from dissolved gases and non-metallic inclusions are presented. The influence of a number of technological features of each method on the quality of the melt has been studied. Examples of equipment for the implementation of processes are presented. To analyze the effectiveness of the use of various technologies for refining aluminum alloys, their ranking was carried out. The results of the analysis are in correlation with the trends in the spread of various processes for the refining of aluminum alloys in foundries. It is shown that blowing the melt with inert gases through a rotating impeller is the most effective in terms of a set of indicators in comparison with other methods.